Análise inelástica avançada de pórticos planos de aço considerando as influências do cisalhamento e de ligações semirrígidas - Renata Gomes Lanna da Silva (2010)
Conventional analysis of steel frames is usually carried out under the assumption that the beam-to-columns connections are either fully rigid or ideally pinned. However, most connections are of type semi-rigid and their behavior lies between these two extreme cases. The semi-rigid connections as well as several geometric and material nonlinearities, influence the bending moment distribution in beams and columns ofstructures. One way to account for all these effects in frame design is using an Inelastic Advanced Analysis. The objective of this work is to present a study of inelastic behaviour of semi-rigid steel frames using advanced analysis, taking into account the Brazilian code prescriptions for checking the strength limit state and serviceability conditions. Inelastic Advanced Analysis developed account for both geometric andmaterial nonlinearities. A geometrically exact finite element formulation to consider material and geometric nonlinearities is presented. The formulation includes P-ä and P-Ä effects and shear strain of members through the Timoshenko theory. The distributed-plasticity analysis includes the spread of plasticity within the cross section and along the member length and residual stresses. Nonlinear spring elements are used to include connections and their behaviour is modelled using multilinearized momentrotation curves. Aiming to use adequately the program developed as a method of Inelastic Advanced Analysis, calibrations are made with the parameters of ABNT NBR 8800:2008. The examples presented are analyzed in order to demonstrate how the Inelastic Advanced Analysis can be used in designing of semi-rigid steelframes.